Brazil : Managing Water Quality - Mainstreaming the Environment in the Water Sector - Margulis, Sergio (Washington, DC: World Bank, 2013)
This study examines how environmental issues have been addressed in the water sector in Brazil, within the context of activities of the Federal Government, generally, and those implemented under Bank sector operations, in particular. The core focus of the study lies in the management of water quality, as it affects both the users of raw water, and those who are primarily concerned with the disposal of wastewater. The report considers the following three sectoral areas concomitantly - water resources management, water supply and sanitation, and, the environment - thus limiting its review, and focus to those themes which are key to the over-arching issue of water quality. Water resources management in the country relied upon heavy investments in medium, and large scale projects that provided basic infrastructure for water uses. However, these have produced questionable impacts in terms of reducing poverty, and inequality. One of the reasons for this, has been the poor infrastructure management, which despite its importance, has been largely underestimated. While improvements in the utilization of existing infrastructure in the water sector remain critical, it needs to be complemented by incentives to both service providers, and water users. Moreover, low economic, environmental, and social returns from investments in the water sector, reflect the tendency to distract attention from the objectives in the design, and implementation of projects. Thus, an assessment of water quality goals is required, which should be based on systematic evaluations of the costs, and benefits of reaching alternative standards, and explicit social objectives.